MARKETING STRATEGIES IMPLEMENTED BY AGEN PERISAI OF BPJS KETENAGAKERJAAN IN BALI PROVINCE - I Nyoman Cakra Wibawa; Gede Sri Darma (Jurnal Ekonomi, 2023)
Perisai agent is an agency program of  BPJS Ketenagakerjaan to educate and acquire BPJS Ketenagakerjaan members.. This research aimed at finding the obstacles faced by Perisai agents in educating and acquiring participants, the roles played by Perisai agents, and the strategies used for members education and acquisition. This research was a qualitative descriptive study using observation and interviews as data collection techniques. There were 10 informants involved in the interviews; 8 informants were Perisai agents in Denpasar, Badung, Gianyar, Bangli and Jembrana while 2 informants were management of the BPJS Ketenagakerjaan Denpasar and Badung. The results of data analysis showed that in carrying out education and acquisitions, Perisai agents encountered obstacles in the form of (1) the lack of information about BPJS Ketenagakerjaan, (2) the public does not understand the importance of job insurance, (3) the bad image of insurance in the eyes of the public, (4) members do not understand the claim process, (5) lack of ability to operate technology, and (6) the issue of corruption in the government. In conducting education and acquisitions, Perisai agents played  roles, namely (1) educator, (2) assistant, (3) payment reminder, and (4) assist with claims. To carry out education and acquisition, several strategies were implemented, such as (1) using social media, (2) providing promos, (3) conducting mass outreach, (4) communicating via telephone, and (5) taking a personal approach.